Cannabis Prevalence and National Drug Policy in 27 Countries: An Analysis of Adolescent Substance Use - Kotlaja, Marijana M. (International journal of offender therapy and comparative criminology, 2019)
Prior research that assesses the relationship between cannabis policy and prevalence rates has yielded mixed results, perhaps due to the varying rigor of these investigations. Addressing some of these issues in rigor and informed by a rational choice theory (RCT), we hypothesize that those policies on the more punitive end of McDonald and colleagues' classification will be most effective. Examining legislation in 27 countries utilizing the Second International Self-Report Delinquency Study (ISRD-2) through hierarchical linear modeling (HLM) models with both individual- and country-level controls, we find little support for these hypotheses. Instead, results from our analysis largely indicate that the variation in country prevalence rates from 2005 to 2007 was not significantly related to cannabis control policy. We comment on possible policy implications for these preliminary results.